A-142 A Correlation between Reading Fluency and Processing Speed in a Child Population. (30th August 2021) - Rifai, Lara; Kajani, Nisha; Kotalik, Kayla; Lopez, Ana; Lashley, Lisa; Golden, Charles J
Abstract: Objective: The aim of this study was to determine whether a correlation exists between reading fluency in the WJ-IV ACH and processing speed in the WISC-V. Method: The data for this study was derived from a large de-identified database. Participants (n = 90) included individuals who completed the Wechsler Intelligence Scale for Children Fifth Edition (WISC-V), which measures intellectual ability, and the Woodcock Johnson IV Tests of Achievement (WJ-IV ACH), which tests for reading, writing, and mathematic achievement. The participants consisted of 36.7% White, 20% Black, 31.1% Hispanic, and 12.2% Other. From the sample, 66.7% were male and 32.3% were female. All the participants were administered the WISC-V and WJ-IV ACH (mean age = 10.53, SD = 2.50; mean education = 4.6, SD = 2.47). Vocabulary was controlled for. Results: The results indicated a significant correlation between the WJ-IV ACH Reading Fluency and the WISC-V Processing Speed Index r(87) = 0.326, p = 0.002. Conclusions: Previous research has found that deficits in processing speed affect reading efficiency. Cognitive processes are affected even in children with ADHD who are able to decode words accurately. Processing speed, specifically Coding in the WISC-IV, was found to be significantly associated with verbal span and measures of working memory. Moreover, processing speed and working memory have been found to be significant predictors of oral reading fluency (Jacobson et al., 2011). The current findings confirm a correlation between processing speed and reading fluency in updated versions of the forementioned assessments. Future research should investigate the role of comorbid diagnosis found in the functioning of both processing speed and reading fluency.